Exceptional Socialists - Bell, D. author. aut Link
XII, 235 p.
Keywords: This engaging exploration of the French Socialist Party details the exceptional problems that the party has faced and the way it has dealt with them. The result is a comprehensive and compelling guide to the quiddities of political infighting, the structure of power and of the environment in which the party operates.